2009
DOI: 10.1120/jacmp.v10i1.2868
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dose evaluation for 3Dimensional conformal partial breast irradiation compared with whole breast irradiation

Abstract: To compare the radiation dose to normal cardiac tissue for 3Dimensional (3D) conformal external beam partial breast irradiation (PBI) and standard whole breast irradiation (WBI), and examine the effect of tumor bed location.For 14 patients with left breast tumors randomized on the National Surgical Adjuvant Breast and Bowel Project B‐39 protocol, computer‐generated radiotherapy treatment plans were devised for WBI and PBI. Tumor bed location was designated according to whether more than 50% of the excision cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Smaller volumes of breast tissue are treated with APBI and, consequently, the incidental dose to the breasts, heart, and lung are also lower. A variety of techniques can be used including, multi-catheter, balloon-catheter and external beam techniques, with accompanying dosimetric studies demonstrating a reduction in low and high dose to the heart and lung (47)(48)(49)(50). Heterogeneous fractionation schedules have been used across studies to treat differing volumes of breast tissue, making interpretation of current data difficult; however, a Cochrane meta-analysis of published phase 3 trials showed inferior normal tissue toxicity and local control with accelerated partial breast irradiation compared to whole breast radiotherapy (50).…”
Section: Accelerated Partial Breast Radiotherapymentioning
confidence: 99%
“…Smaller volumes of breast tissue are treated with APBI and, consequently, the incidental dose to the breasts, heart, and lung are also lower. A variety of techniques can be used including, multi-catheter, balloon-catheter and external beam techniques, with accompanying dosimetric studies demonstrating a reduction in low and high dose to the heart and lung (47)(48)(49)(50). Heterogeneous fractionation schedules have been used across studies to treat differing volumes of breast tissue, making interpretation of current data difficult; however, a Cochrane meta-analysis of published phase 3 trials showed inferior normal tissue toxicity and local control with accelerated partial breast irradiation compared to whole breast radiotherapy (50).…”
Section: Accelerated Partial Breast Radiotherapymentioning
confidence: 99%